Prinzmetal Angina: A Case of Recurrent Ventricular Fibrillation - Gujejiani, Lali; Latsuzbaia, Kakhaber; Tsivilashvili, Jaba; Jalabadze, Khatuna; Kharebashvili, Maia; Jinjolia, Nato; Tetradze, Vakhtang; Taboridze, Iamze (European Scientific Journal, ESJ, 2026)
Prinzmetal angina (also known as vasospastic or variant angina) is characterized by episodic coronary artery spasms, leading to transient ischemia and angina, often accompanied by ST elevation on ECG. While typically non-myocardial infarction in nature, severe cases can progress to life-threatening complications such as ventricular fibrillation (VF). This report details the case of a 66-year-old male with hypertension and a history of aortic root replacement, presenting with recurrent VF secondary to coronary vasospasm despite optimal medical therapy. ECG showed ST elevation, and coronary angiography revealed moderate stenosis with severe vasospasm. Despite treatment with vasodilators, the patient experienced persistent arrhythmias, necessitating multiple defibrillations. Coronary stenting of the affected arteries ultimately led to stabilization. This case highlights the challenges of managing refractory arrhythmias in VA and underscores the potential role of interventional therapy when medical management fails.